A multiplicity result for a semilinear Maxwell type equation - Azzollini, Antonio (Topological Methods in Nonlinear Analysis, 2008)
In this paper we look for solutions of the equation δ dA=f’(A,A)Ain R^2k, where A is a 1-differential form and k≥ 2. These solutions are critical points of a functional which is strongly indefinite because of the presence of the differential operator δ d. We prove that, assuming a suitable convexity condition on the nonlinearity, the equation possesses infinitely many finite energy solutions.